Modelagem de planilha eletrônica para dimensionamento de sapatas rígidas isoladas retangulares - Carvalho, Jesmiel Héber Freire de (Universidade Federal Rural do Semi-Árido, 2021)
The use of tools that help and streamline the engineering design process are essential for today, the big problem is that most of them require an initial financial investment that is beyond the reach of many people, especially recently graduated engineers or students still in formation. The present work aimed to develop an electronic spreadsheet for sizing rectangular rigid insulated shoes, in an automated way, through computational modeling processes, that is, to provide a tool that processes data quickly with satisfactory results, whose cost and use acquisition costs are minimal compared to other similar ones. In order for the program to fully fulfill its function, it was programmed so that the geometric dimensions of the insulated shoe type foundation element with a rectangular shape and rigid structure behavior were determined, as well as its reinforcement, based on the characteristics of the soil and that meets the requirements of the current standard and also allows the generation of a detail in plan and view of the dimensioned elements plus a table of quantities of materials to be used. For its development, a theoretical survey on the subject was carried out in materials such as technical handouts, books and academic research papers with similar themes and ideas and from this, a flowchart of the dimensioning steps was elaborated, followed by the creation of the interface and visualization design. In the present work, it was possible to conclude that the tool can be used in both professional and academic fields, despite its limitations of covering only one type of specific structural element, but that it can be improved at the user's discretion or even extended to others types of existing foundations
Keywords: Fundações; Sapatas; Planilha Eletrônica; Foundations; Shallow Foundation; Spreadsheet; ENGENHARIAS::ENGENHARIA CIVIL